Sīriešu Jaunās Derības dažu grāmatu leksiskā atslēga - Zeps, Dainis (My University, 2011)
Lexical Key to some books (Matthew 2-14,Gallatians, Titus) of Syriac New Testament in Latvian.
Keywords: Syriac language; Syriac New Testament; Lexical key in Latvian